A Study on the Determinats of Credit Risk in Malaysian Banking System for the Period 1996 to 2017 - Kar Yi, Wong; Abdullah Bin Megat Mahmud, Megat; A/L Suppiah, Thirunavukkarasu (International Journal of Psychosocial Rehabilitation, 2020)
Given the rising bankruptcy cases in Malaysia, the significance of credit risk management acquires more awareness from the society and banking industry, resulting in the establishment of countless research papers related to the issue of credit risk management. Nevertheless, the factors that bring an impact on the credit risk in banks are less researched and analyzed. Therefore, this study seeks to examine the determinants of credit risk in Malaysian banking system for the period 1996 to 2017. The selected variables are gross domestic product (GDP), unemployment rate, inflation rate, interest rate and management efficiency. This study applies autoregressive distributed lag (ARDL). The sampling frame consists of 26 Malaysian commercial banks. The research findings show that all the variables are manifested to have a significant relationship with the credit risks in Malaysian banking system. These research findings enable the practitioners to solve the issue of credit risks more productively. Bank officers could also implement a more fruitful credit risk management system after perceiving the causes of escalating credit risk in banking industry.